Microglia: Key Players in Retinal Ageing and Neurodegeneration - Guo, Li; Choi, Soyoung; Bikkannavar, Priyanka; Cordeiro, M. Francesca (Frontiers in Cellular Neuroscience, 2022)
Microglia are the resident immune cells of the central nervous system (CNS) and play a key role in maintaining the normal function of the retina and brain. During early development, microglia migrate into the retina, transform into a highly ramified phenotype, and scan their environment constantly. Microglia can be activated by any homeostatic disturbance that may endanger neurons and threaten tissue integrity. Once activated, the young microglia exhibit a high diversity in their phenotypes as well as their functions, which relate to either beneficial or harmful consequences. Microglial activation is associated with the release of cytokines, chemokines, and growth factors that can determine pathological outcomes. As the professional phagocytes in the retina, microglia are responsible for the clearance of pathogens, dead cells, and protein aggregates. However, their phenotypic diversity and phagocytic capacity is compromised with ageing. This may result in the accumulation of protein aggregates and myelin debris leading to retinal neuroinflammation and neurodegeneration. In this review, we describe microglial phenotypes and functions in the context of the young and ageing retina, and the mechanisms underlying changes in ageing. Additionally, we review microglia-mediated retinal neuroinflammation and discuss the mechanisms of microglial involvement in retinal neurodegenerative diseases.